Effective photocatalytic and bifunctional electrocatalytic materials based on Keggin arsenomolybdates and different transition metal capped assemblies. Issue 25 (5th June 2018) - Li, Feng-rui; Lv, Jing-hua; Yu, Kai; Zhang, Mao-lin; Wang, Kun-peng; Meng, Fan-xue; Zhou, Bai-bin
Abstract : V, Co, and Cu were introduced into AsMo12 system to build three Keggin derivatives with different caps, which show excellent photocatalytic activity and bifunctional electrocatalytic behavior. Abstract : Three novel Keggin arsenomolybdates with transition metal modifying caps, (Hbimb)(H2 bimb)[AsMoVI8VV4Co2 O40 ] (1 ), (Hbimb)2 (H2 bimb)0.5 [AsMoVI8VV4Cu2 O40 ]·1.5H2 O (2 ), and [Cu I (imi)2 ][{Cu I (imi)2 }4 {AsMoV6VVI6O40 (VIV2O2 )}] (3 ) (bimb = 1, 4-bis(imidazol-l-yl)butane; imi = imidazole), were obtained via altering the solution pH and the organic ligands in the reaction system, and were characterized via routine techniques. Compounds1 and2 are tetra-vanadium substituted AsMoVI8VV4O40 clusters capped by two Co 2+ or Cu 2+ cations at two symmetrical pit positions of two opposite Mo4 O18 tetramers, and these represent the first tetra-vanadium substituted bi-cobalt(ii )/copper(ii ) capped assemblies. The basic unit of compound3 is one hexa-electron-reduced Keggin polyoxoanion AsMoV6MoVI6O40 capped by two VO5 units at the same positions. The adjacent basic units were bonded together via the square binuclear linker {Cu2 (imi)4 O2 } to yield an infinite 1D cap-to-cap chain, which was further aggregated together in A–B–A–B mode via a pair of {Cu(1)(imi)2 } linkers, forming an unique 2D layer. Compounds1–3 show bifunctional electrocatalytic character and effective photocatalytic performance toward the degradation of typical dyes under UV irradiation.